L2 Enjoyment of English as a Foreign Language Students: Does Teacher Verbal and Non-verbal Immediacy Matter? - Guo, Hongyu; Gao, Wurong; Shen, Yumin (Frontiers in Psychology, 2022)
This review explored the investigations on the role of teacher immediacy in English as a Foreign Language (EFL) learners’ foreign language enjoyment. Earlier investigations have proved that teacher immediacy, such as posture, body language, vocal variety, gestures, and smile, can significantly affect learners’ positive emotions like foreign language enjoyment. It means that teachers should try both to control the feelings of their learners and manage their feelings to enhance enjoyment among learners. Moreover, studies have shown that teacher immediacy is significantly related to learner motivation which is a basis for increasing foreign language enjoyment among learners. However, specific strategies can be employed to increase learner motivation, which in return increases learner foreign language enjoyment. Furthermore, the study presented the implications and future directions of this line of research for different people, such as EFL teachers, teacher educators, and foreign language scholars. The ideas can improve their awareness of teacher-student relationships, in particular, teacher immediacy and its role in learners’ foreign language enjoyment.